Randomized trial of dentists' understanding: treatment benefit in absolute numbers vs relative risk reduction - Paulo NADANOVSKY; Branca Heloisa de OLIVEIRA; Ronaldo LIRA-JUNIOR; Ana Paula Pires dos SANTOS (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study aimed to assess whether dentists correctly understand the benefit of a dental treatment when it is presented using absolute numbers or relative risk reduction (RRR). This parallel-group randomized controlled trial recruited dentists from 3 postgraduate courses in Rio de Janeiro, Brazil. Participants received, in sequentially numbered sealed opaque envelopes, the description of a hypothetical scenario of the benefit (avoidance of multiple tooth loss) of nonsurgical periodontal treatment without or with antibiotics. Treatment benefit was presented in 2 different formats: absolute numbers or RRR. Dentists were given 10 minutes to read the treatment scenario and answer 5 questions. The final sample for analysis included 101 dentists. When asked to estimate the number of patients out of 100 who would avoid multiple tooth loss without antibiotics, 17 dentists (33%) in the absolute numbers group and 12 (25%) in the RRR group provided the correct response (p = 0.39). Regarding treatment with antibiotics, 26 dentists (50%) in the absolute numbers group and 14 (29%) in the RRR group provided the correct response (p = 0.04). Only 16 dentists (31%) in the absolute numbers group and 12 (25%) in the RRR group gave correct answers for both questions (p = 0.51). Most dentists did not correctly understand the benefit of the treatment, irrespective of the format it was presented. Slightly more dentists correctly understood the benefit of the treatment when it was presented as absolute numbers than as RRR.